Regulation of Hepatic Drug Transporter Activity and Expression by Organochlorine Pesticides. Issue 3 (27th November 2013) - Bucher, Simon; Le Vee, Marc; Jouan, Elodie; Fardel, Olivier
ABSTRACT Organochlorine (OC) pesticides constitute a major class of persistent and toxic organic pollutants, known to modulate drug‐detoxifying enzymes. In the present study, OCs were demonstrated to also alter the activity and expression of human hepatic drug transporters. Activity of the sinusoidal influx transporter OCT1 (organic cation transporter 1) was thus inhibited by endosulfan, chlordane, heptachlor, lindane, and dieldrine, but not by dichlorodiphenyltrichloroethane isomers, whereas those of the canalicular efflux pumps MRP2 (multidrug resistance‐associated protein 2) and BCRP (breast cancer resistance protein) were blocked by endosulfan, chlordane, heptachlor, and chlordecone; this latter OC additionally inhibited the multidrug resistance gene 1 (MDR1)/P‐glycoprotein (P‐gp) activity. OCs, except endosulfan, were next found to induce MDR1/P‐gp and MRP2 mRNA expressions in hepatoma HepaRG cells; some of them also upregulated BCRP. By contrast, expression of sinusoidal transporters was not impaired (organic anion‐transporting polypeptide (OATP) 1B1 and OATP2B1) or was downregulated (sodium taurocholate co‐transporting polypeptide (NTCP) and OCT1). Such regulations of drug transporter activity and expression, depending on the respective nature of OCs and transporters, may contribute to the toxicity of OC pesticides.